Information Storage in Permalloy Modulated Magnetic Nanowires - Escrig-Murua, J (Nature Research, 2021)
A long piece of magnetic material shaped as a central cylindrical wire (diameter d= 50 nm) with two wider coaxial cylindrical portions (diameter D= 90 nm and thickness t= 100 nm) defines a bimodulated nanowire. Micromagnetism is invoked to study the equilibrium energy of the system under the variations of the positions of the modulations along the wire. The system can be thought of as composed of five independent elements (3 segments and 2 modulations) leading to 2 5= 32 possible different magnetic configurations, which will be later simplified to 4. We investigate the stability of the configurations depending on the positions of the modulations. The relative chirality of the modulations has negligible contributions to the energy and they have no effect on the stability of the stored configuration. However, the modulations are extremely important in pinning the domain walls that lead to consider each segment as independent from the rest. A phase diagram reporting the stability of the inscribed magnetic configurations is produced. The stability of the system was then tested under the action of external magnetic fields and it was found that more than 50 mT are necessary to alter the inscribed information. The main purpose of this paper is to find whether a prototype like this can be complemented to be used as a magnetic key or to store information in the form of firmware. Present results indicate that both possibilities are feasible. © 2021, The Author(s).